Effects of Different Methods of Isolation on Volatile Composition of Artemisia annua L. - Danijela Vidic; Amira Čopra-Janićijević; Mladen Miloš; Milka Maksimović (International Journal of Analytical Chemistry)
In order to determine influence of extraction method on volatile oil composition of Artemisia annua L., steam distillation, hydrodistillation, organic solvent extraction, and headspace sampling have been applied. The relative abundance of volatile compounds from the odorous aerial parts of A. annua, obtained by different extraction techniques, was analyzed by GC-MS. Exactly fifty constituents were identified. The leaf and flower essential oil yield ranged from 0.9 to 2.3% (v/w). Oxygenated monoterpenes were predominant in all samples ranged from 42.6% for steam-distilled fraction of petroleum ether extract to 70.6% for headspace of plant material. Essential oils isolated by steam distillation and hydrodistillation indicate that A. annua belongs to artemisia ketone chemotype with its relative content of 30.2% and 28.3%, respectively. The principal constituent in headspace sample of plant material was also artemisia ketone (46.4%), while headspace of petroleum ether extract had camphene (25.6%) as the major compound. The results prove the combined approaches to be powerful for the analysis of complex herbal samples.